The oretical-legal aspect of state service in the Russian Federation subjects - A. V. Tarakanov (Russian Journal of Economics and Law)
Objective: to define the oretical-legal aspect of state service in the Russian Federation subjects. Methods: cognitive approach to cognition of the essence of state service. Results: Basing on the analysis of normative-legal acts, the basic sense of the legal aspect of state service is studied; the key positions of efficient service functioning are viewed, as well as the summarized requirements to the state authorities’ apparatus. Scientific novelty: the article for the first time proposes solutions of the following tasks: implementation of the Constitution and laws of the Russian Federation and its subjects; ensuring national security taking into account the interests of the regions, state sovereignty, economic independence, spiritual-moral identity of nations; legal regulation of activity based on special legislation as a unity of legal norms, rules and procedures, concerning the relations connected with state service organization. Practical value: The main provisions and conclusions of the article can be used in scientific and educational activity when viewing issues of the essence and trends of Constitutional Law development.